The Swiss Brain Health Plan 2023–2033 - Claudio L. A. Bassetti; Mirjam R. Heldner; Kristina Adorjan; Emiliano Albanese; Gilles Allali; Marcel Arnold; Indrit Bègue; Murielle Bochud; Andrew Chan; Kim Q. do Cuénod; Renaud Du Pasquier; Bogdan Draganski; et al. (Clinical and Translational Neuroscience, 2023)
The brain and its health are essential for our (physical mental, social, and spiritual) wellbeing, for being able to realize our potential as individuals, and also for a fair, well-functioning, and productive society. However, today the world is facing a healthcare crisis related to the very high (and increasing) burden of brain disorders. As a response to this crisis, the “Swiss Brain Health Plan” (SBHP) was conceptualized in the context of other initiatives launched to value, promote, and protect brain health over the entire life course. In the first section of this position paper, the following fundamental considerations of the SBHP are discussed: (1) the high (and increasing) burden of brain disorders in terms of prevalence (>50% of the population suffers from a brain disorder), disability, mortality, and costs; (2) the prevention of brain disorders; (3) the operational definition of brain health; (4) determinants of brain health; (5) international initiatives to promote brain (including mental) health including the World Health Organization (WHO) intersectorial global action plan on epilepsy and other neurological disorders (NDs) (IGAP) and the WHO comprehensive mental health action plan. In the second section of the paper, the five strategic objectives of the SBHP, which has the vision of promoting brain health for all across the entire life course, are presented: (1) to raise awareness; (2) strengthen cross-disciplinary and interprofessional training/educational programs for healthcare professionals; (3) foster research on brain health determinants and individualized prevention of brain disorders; (4) prioritize a holistic (non-disease-specific), integrated, person-centered public health approach to promote brain health and prevent brain disorders through collaborations across scientific, health care, commercial, societal and governmental stakeholders and insurance providers; (5) support, empower, and engage patients, caregivers, and patient organizations, and reduce the stigma and discrimination related to brain disorders. In the third section of the paper, the first (2024) steps in the implementation of the SHBP, which will be officially launched in Zurich on 22 November 2023, are presented: (1) a definition of the overall organization, governance, specific targets, and action areas of the SBHP; (2) the patronage and/or co-organization of events on such specific topics as brain research (Lausanne), dementia (Geneva), stroke (Basel), neurohumanities (Bellinzona), sleep (Lugano), and psychiatry (Zurich); (3) the conduction of a new study on the global burden of brain disorders in Switzerland; (4) the launching of an international Certificate of Advanced Studies (CAS) on Brain Health at the University of Bern. In the fourth section of the paper, there is a concise executive summary of the SBHP.